Effect of the zinc salt concentration on the ZnO thin films properties grown by MWCBD. (30th November 2018) - Galeazzi, R; González-Panzo, I J; Díaz, T; Silva, R; Morales, C; Rosendo, E; Romano, R; García, G; Gutiérrez, D R
Abstract: Nanostructured ZnO thin films with different surface morphologies have been synthesized by the microwave assisted chemical bath deposition technique (MWCBD), adjusting the pH of the reaction solution between 9 and 11.14. Newest results are presented in this work supported by previous investigations. Morphology, structure and optical properties of the films have been studied by scanning electron microscopy (SEM), x-ray diffraction (XRD) and room temperature photoluminescence (PL) techniques. It has been observed that the zinc salt concentration and the pH of the reaction solution determines the reaction kinetics, affecting strongly the morphology of the final product. However, the rapid heating in microwave irradiation process facilitates the crystallization of the formed nano-/microstructures. Effects of composition and morphology of the grown nano-/microstructures on their photoluminescence (PL) behaviors have been discussed.